2020
DOI: 10.1002/pat.5021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ultra‐high concentration of salt‐resistant polyacrylamide

Abstract: Glucose, an environmentally friendly and renewable material, is modified differently in various fields. In the petrochemical industry, water-soluble polymer with salt resistance plays an important role in the production in high-salinity reservoirs. In this work, N,N-dimethyl ethanolamine was reacted with glucose to synthesis a polymerizable monomer Gf (N,N-dimethylaminoethylglucoside). Gf was polymerized with acrylamide in aqueous solution to obtain copolymer glucose modified polyacrylamide. The copolymer was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Consequently, viscosity generation transitions from occurring within individual molecules to taking place between multiple molecules. This shift is responsible for the observed increase in viscosity . Polymers containing hydrophobic monomers exhibit not only hydrogen bonds between molecules but also hydrophobic associations among the hydrophobic monomers.…”
Section: Resultsmentioning
confidence: 96%
“…Consequently, viscosity generation transitions from occurring within individual molecules to taking place between multiple molecules. This shift is responsible for the observed increase in viscosity . Polymers containing hydrophobic monomers exhibit not only hydrogen bonds between molecules but also hydrophobic associations among the hydrophobic monomers.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, the supramolecular system based on hydrogen bonding has also been gradually applied to tertiary oil recovery. Zhao et al [ 149 ] synthesized a polymerizable monomer GF (N-dimethylaminoethyl glucoside) with glucose and then polymerized with acrylamide to obtain an environmentally friendly oil displacement polymer ( Figure 9 C). Under the harsh environment of 200 g/L mineralization, the system can still maintain high viscosity.…”
Section: Application Progress Of Supramolecular Polymers In Eormentioning
confidence: 99%
“…( B ) The supramolecular polymer based on host–guest interaction has the phenomenon of salt thickening [ 35 , 37 , 95 ]. ( C ) Due to the coordination between hydrogen bond and metal, HPAM with a glucoside unit showed super high salt tolerance [ 149 ]. ( D ) Introducing bases into the side chain of HPAM [ 150 ].…”
Section: Figurementioning
confidence: 99%
“…They found that UHMW HPAMs can acquire stronger flow resistance in porous medium than HAPM, and the ability of alkaline–surfactant–polymer (ASP) flooding based on UHMW‐HPAM to increase oil recovery is far better than that of an ASP system based on ordinary HPAM. (2) Temperature and salt tolerant groups are introduced into the polymer molecular chain 31,32 . Zhao 33 synthesized a temperature‐resistant functional monomer (TEPA) and a hydrophobically associating salt‐resistant monomer (APC).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Temperature and salt tolerant groups are introduced into the polymer molecular chain. 31,32 Zhao 33 synthesized a temperature-resistant functional monomer (TEPA) and a hydrophobically associating salt-resistant monomer (APC). These functional monomers are polymerized with acrylamide (AM) and acrylic acid (AA) to prepare a temperature-resistant and salt-resistant poly(AM) oil-displacement agent (AATA) with siloxane groups.…”
Section: Introductionmentioning
confidence: 99%